Solid Waste Disposal: A Potential Threat to Aquatic Environment - , Chidinma Acholonu, E. Diagi Bridget, Nwufo Remigus Somtochukwu, Ekweogu Chinonye, Justin N. Okorondu, Chijioke Uyo (Archives of Current Research International, 2023)
The disposal of solid waste close to water bodies is becoming a threat to the potability of water and the survival of aquatic organism. This research work was carried out to assess the impact of solid waste disposal on Nwaorie River in Owerri, Imo State, Nigeria. This was to ascertain the level of some heavy metals and physico-chemical parameters that could affects the quality of the water. Three sampling stations were established along the length of the study area and water from untreated effluent discharged points, 50m upstream, 50m midstream and 50m downstream respectively from the point of discharge. The water sample collected was taken to the Laboratory for analysis. Parameters such as pH, turbidity, Temperature, Total Dissolved Solid, Electrical conductivity, Dissolved Oxygen, Zinc, Arsenic, Iron, Cadmium were measured in situ using a multi-parameter water quality monitor and flame absorption spectrometry. The results obtained revealed the concentration of dissolved Oxygen ranged 6.900-7.400mg/l, Biochemical Oxygen Demand ranged 0.250-0.540mg/l, mean of pH has the highest value of 5.30±0.0 at the downstream, electrical conductivity highest value was 98.00±0.0 at the downstream and temperature was found highest at the upstream with a value of 31.2±0.01 Zinc was less than 0.003mg/l in all sampling points, Iron, zinc and Arsenic were not detected while CaCO3 ranged 13-29mg/l and turbidity was 0.00. When compared the results of the measured parameters with World Health Organization Standard, all the measured parameter fell within the permissible limit. The study therefore concluded that river Nwaorie is slightly impacted by untreated waste deposited within the vicinity of the river, which could have implications for people that depend on the river for domestic uses and also aquatic organism in the river. Measures should therefore, be taken to stop this unhealthy way of waste disposal.